Learning loss experience and control motive by Zillennial generation in Indonesia - Bagas Narendra Parahita; Dwi Astutik; Ghufronudin Ghufronudin; Yuhastina Yuhastina (Institute of Advanced Engineering and Science, 2023)
The development of the COVID-19 situation in Indonesia affected particularly education sector in Indonesia significantly when learning loss occurs. The majority of students forced to attend online learning during the pandemic era are Generation Z (Gen Z). Gen Z is viewed as a digital natives group that can adapt quickly to online learning, but independent online learning situations make Gen Z vulnerable to experiencing learning loss. It will be interesting to find out the process of controlling learning loss done by Gen Z as digital natives. This research used a qualitative method with a phenomenological approach. The main informant consisted of 32 students selected purposively with the criteria of those born in 2000-2008. Few in-depth interviews were conducted offline and the majority of them are conducted online. The finding of research shows particularly that the experience of Zillennial generation group (cohort) with online learning before the pandemic (Because-motives) and during the pandemic can equip them to control learning loss they feel conscious (In-order-to-motive). Another finding leads to the creation of three Gen Z Typications in online learning during the pandemic time including inconsistent, proactive, learning independence, and desperation Typication. Generation Z group exists as one generation consciously experiencing loss of learning during pandemic incidence.